Augmenting Consumer Acceptance of Robot-Assisted Technologies in Retail Industry: An Interdisciplinary Approach - M, Khalufi Nasser Ali (Journal of Accounting, Business and Management (JABM), 2024)
Since they have been incorporated into retail, robots have been discussed more frequently in academic publications and public debate. Customers in retail sector, as well as workers will be resistant to the rising employment of robots as their capabilities increase and they are employed to supplement or replace human labour. "Interdisciplinary" denotes a technique that amalgamates knowledge and methodologies from several academic or professional domains to attain a thorough comprehension of a particular subject or matter. As robots and AI become more common in society, this study examines the public's attitudes towards their use in retail. Consumer perceptions of retail robots are examined using consumer psychology and technology attitudes literature. To fill the research gap, 393 retailers' responses on service robot deployment in retail contexts are analyzed, with an emphasis on the East region. Service robot attitudes vary based on aspects such as robot benefits, social skills, and technology attitudes. Cluster analysis divides respondents into "high techies" and "high touches," depending on their service robot acceptance. The regression study clarifies how numerous factors affect retail robot-assisted service perceptions. Retailers and policymakers can learn from the survey that consumer opinion is significant for the future integration of robots in retail.